RARE-51. RITUXIMAB, METHOTREXATE, BCNU, ETOPOSIDE, AND PREDNISONE (RMBVP) FOR THE TREATMENT OF RELAPSED/RECURRENT PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA: A RETROSPECTIVE SINGLE CENTER STUDY. (11th November 2019) - Reiss, Samantha; Yerram, Prakirthi; Modelevsky, Lisa; Grommes, Christian
Abstract: BACKGROUND: Primary Central Nervous System Lymphoma (PCNSL) is an aggressive rare non-Hodgkin lymphoma. Prognosis is particularly poor for relapsed/recurrent (R/R) patients with no established treatment modality. Methotrexate/BCNU/Teniposide/Prednisone with or without rituximab has efficacy in newly diagnosed PCNSL. Here, we report efficacy and toxicity of RMBVP for the treatment of R/R PCNSL. METHODS: This retrospective study at MSKCC included PCNSLs treated with MBVP for R/R disease between 5/2009 and 5/2019. Methotrexate (3.5 g/m2; day 1 and 15), etoposide (100 mg/m2; day 2), BCNU (100 mg/m2; day 3), prednisone (60 mg/m2/day; day 1–5) and rituximab (500 mg/m2; day 0 and 14) were given in 28-day cycles. Granulocyte colony-stimulating factor support was given for 5 days in between doses of chemotherapy. RESULTS: Thirty patients received MBVP; 27 (90%) received RMBVP with a median of 2 cycles given (0.5–5). Median age was 66 years (23–81); median KPS was 70 (30–90); 14 (46.7%) were women. Median prior lines of therapy were 2 (1–5); all received prior methotrexate. Median time from last treatment was 1 month (0–88.3; 21 (70%) < 12 months). Of twenty-nine evaluable patients for response, 23 (76.7%) had a response (9 complete response (CR) (30%), 5 CR-unconfirmed (16.7%), 8 partial response (26.7%), 1 stable disease (3%)). At a median follow up of 14.2 months, median progression free survival (PFS) was 15.6 months and median overall survival was not reached. Median PFS was poorer for patients with < 12 months since last chemotherapy, 10.1 vs 60.6 months. Rates of serious (grade 3 or 4) neutropenia, anemia, thrombocytopenia and transaminitis were 20%, 20%, 16.7%, and 16.7%, respectively. One patient experienced grade 3 nephrotoxicity. No treatment related mortalities occurred. CONCLUSIONS: RMBVP is a tolerable treatment option for R/R PCNSL, particularly in those with recurrent disease.